PELESTARIAN NILAI-NILAI BUDAYA PADA PENDIDIKAN ANAK USIA DINI SANDAT KUNING DI KARANG MEDAIN BARAT KOTA MATARAM - I Nyoman Murba Widana (Widya Sandhi: Jurnal Kajian Agama, Sosial dan Budaya, 2018)
This research aims to study the cultivation of cultural values conducted on the Early Childhood Education Sandat Kuning, Karang Medain Barat Village, Mataram City. This study used descriptive interpretive method in order to conduct a study on the planting of these values. The results showed that the planting of cultural values in the institution of early childhood education Sandat Kuning using game approach in order to build habituation of learners to know the culture. The introduction of the culture is then aimed at preserving the familiar culture in everyday life. It is expected to build an understanding of the importance of cultural values inherited by their ancestors in realizing a better life.